Science Process Skills in Science Education: A Systematic Literature Review on Conceptual Frameworks, Assessment Approaches, and Instructional Strategies (2010--2026) - Irfan Ananda Ismail; Refitaniza (Indonesian Journal of Chemical Connections, 2026)
Background: Science process skills (SPS) are foundational for scientific inquiry, yet their conceptualization, assessment, and instruction remain fragmented. Objective: This systematic review synthesizes empirical re- search on SPS across three dimensions: conceptual frameworks, assessment instruments, and instructional strategies. Methods: A PRISMA-guided search of Scopus, ERIC, Web of Science, and Google Scholar yielded 52 studies published between 2010 and 2026. Thematic synthesis and quality appraisal using a modified MMAT checklist were employed. Results: Frameworks consistently distinguish basic from integrated SPS, but opera- tional definitions vary. Assessment has shifted from multiple-choice tests toward Rasch-validated performance rubrics, though classroom adoption lags. Guided inquiry and POGIL are the most empirically supported strategies, yet effect sizes are moderated by teacher expertise, resources, and cultural context. Conclusion: Coherent, evidence-based frameworks integrating cognitive and sociocultural perspectives are needed. Future research requires longitudinal designs, cross-cultural instrument validation, and replication studies with adequate statistical power.